The money diaries of the “fair sex” in the second half of the “long” 19th century (Theatrum historiae, 2010)
The structure of expenses depended on the amount of money the husband brought into the family. This money was not always enough – something which was true not only of the 19th century. Women always worked side by side with their husbands and contributed to the family income. They also generally managed the housekeeping money. In the 19th century the basic expenses were on rent, money for food, fuel for heating, school fees, and essential outlay on medical treatment, clothing, and clothing maintenance. They had to think about old age, sudden death, or misfortunes that could occur with their property: this was when insurance first originated. We can get an insight into the structure of expenses of individual families primarily from sources of a personal nature, such as wills, memoirs, personal diaries and private correspondence, although especially from household money diaries, which most women kept. Only a few of these have been preserved, although enough to allow us to say that consumption was not only determined by social status and the financial resources of the family, but also by where they lived. The consumption habits of urban families differed from those of rural families; much less food was bought in villages. Buying habits were influenced by the season of the year, with autumn in particular costing more. People shopped differently on weekdays, differently on Fridays and other fasting days, and differently on Sundays: people shopped on a daily basis, and foods, with the exception of long-lasting goods, were not stocked up on: milk, meat, bread and vegetables needed to be bought every day. Expenses on fancy goods, such as southern fruit, luxury smoked meats or chocolate, were rare. From the end of the 19th century women began to become involved on the labour market.